Highly zone-dependent synthesis of different carbon nanostructures using plasma-enhanced arc discharge technique - Kumar R.; Singh R.K.; Dubey P.K.; Yadav R.M.; Singh D.P.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
Three kinds of carbon nanostructures, i.e., graphene nanoflakes (GNFs), multi walled carbon nanotubes (MWCNTs), and spherical carbon nanoparticles (SCNPs) were comparatively investigated in one run experiment. These carbon nanostructures are located at specific location inside the direct current plasma-assisted arc discharge chamber. These carbon nanomaterials have been successfully synthesized using graphite as arcing electrodes at 400 torr in helium (He) atmosphere. The SCNPs were found in the deposits formed on the cathode holder, in which highly curled graphitic structure are found in majority. The diameter varies from 20 to 60 nm and it also appears that these particles are self-assembled to each other. The MWCNTs with the diameter of 10–30 nm were obtained which were present inside the swelling portion of cathode deposited. These MWCNTs have 14–18 graphitic layers with 3.59 Å interlayer spacing. The GNFs have average lateral sizes of 1–5 μm and few of them are stacked layers and shows crumpled like structure. The GNFs are more stable at low temperature (low mass loss) but SCNPs have low mass loss at high temperature. © 2015, Springer Science+Business Media Dordrecht.